(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The fundamental premise behind this notion is that the Internet is present all around us in the form of a variety of items or objects such as mobile phones, computers, and everyday goods such as refrigerators, TVs, and smart sensors. The idea of the Internet of Things shortly referred to as an IoT was driven by technological advancements that allowed effective wireless small devices. Between 2015 and 2020, mobile data traffic is projected to increase eightfold, and the number of mobile connected devices will reach 11.6 billion. The integration of several technologies and communications solutions, such as wired and wireless sensor and actuator networks, next-generation communication protocols, identification technologies, and artificial intelligence for smart objects, are key factors in this exponential growth and widespread acceptance. We analyze the role of the Internet of Things in different areas, consider technical issues, and assess the problems and possibilities that the Internet of Things presents in this paper.